Working When No One Is Watching: Motivation, Test Scores, and Economic Success - Segal, Carmit (Management Science, 2012)
This paper provides evidence that scores on simple, low-stakes tests are associated with future economic success because the scores also reflect test takers' personality traits associated with their level of intrinsic motivation. To establish this, I use the coding speed test that was administered without incentives to participants in the National Longitudinal Survey of Youth (NLSY). I show that, controlling for cognitive ability, the coding speed scores are correlated with future earnings of male NLSY participants. I provide evidence that the coding speed scores relate to intrinsic motivation. I show that the scores of the highly motivated, though less educated, group (potential recruits to the U.S. military), are higher than the NLSY participants' scores. I use controlled experiments to show directly that intrinsic motivation is an important component of the unincentivized coding speed scores and that it relates to test takers' personality traits. This paper was accepted by Teck Ho, behavioral economics.